Dynamin- and Rab5-dependent endocytosis is required to prevent Drosophila photoreceptor degeneration. - Pinal, N.; Pichaud, F. (Journal of Cell Science, 2011)
In Drosophila photoreceptors, Rhodopsin 1 (ninaE, Rh1) is required for proper morphogenesis and maintenance of the apical light-gathering organelle, the rhabdomere. It has been proposed that Rh1, coupled to the Rho GTPases Rac1 and Cdc42, promotes the morphogenesis of a sub-rhabdomeric F-actin meshwork or rhabdomere terminal web (RTW). The RTW provides mechanical support to the apical microvilli and is likely to guide Rab11-dependent delivery of Rh1-rich membrane to the rhabdomere from the trans Golgi network. However, the nature and function of the molecular pathway involved in RTW morphogenesis remains incomplete. Here, we show that Rh1 function in promoting RTW morphogenesis is light-independent and is conserved throughout evolution. This Rh1 function does not require G(q)?(e), which is required for phototransduction. Finally, we show that interfering with Dynamin- and Rab5-dependent endocytosis leads to a phenotype that is undistinguishable from that of the ninaE-null mutant. Importantly, the corresponding endocytic activity is essential to prevent early onset of rhabdomere degeneration. In conclusion, we propose that Rh1 function in promoting RTW morphogenesis is not only needed to sustain apical membrane delivery but is also required for proper rhabdomeric membrane endocytosis and turnover.